Characterization of a high-purity germanium detector for small-animal SPECT - Johnson, Lindsay C (2011)
We present an initial evaluation of a mechanically-cooled, high-purity germanium double-sided strip detector as a potential gamma camera for small-animal SPECT. It is 90 mm in diameter and 10 mm thick with two sets of 16 orthogonal strips that have a 4.5 mm width with a 5 mm pitch. We found an energy resolution of 0.96% at 140 keV, an intrinsic efficiency of 43.3% at 122 keV and a FWHM spatial resolution of approximately 1.5 mm. We demonstrated depth-of-interaction estimation capability through comparison of pinhole acquisitions with a point source on and off axis. Finally, a flood-corrected-flood image exhibited a strip-level uniformity of less than 1%. This high-purity germanium offers many desirable properties for small-animal SPECT.